Meiobenthic community in vegetative areas at Sungai Pulai estuary, Johor, Malaysia - Kassim, Zaleha; Mohd Fathi, Farah Diyana; Yunus, Kamaruzzaman; John, Akbar (Malayan Nature Society, 2015)
Sungai Pulai is blessed with seagrass beds and mangroves but at the same time exposed to the increasing industrial activities in the Straits of Johor. Samples of sediment were collected during the low tide to investigate the contribution of vegetative bottom to the community of meiobenthos and harpacticoid copepods inhabiting the estuary.Three areas, starting from the outer part of the estuary toward the river;Merambong seagrass bed, Merambong Island and Sungai Duku were chosen for the study. Salinity and dissolved oxygen is significantly different (p<0.05) between the Merambong areas and Sungai Duku, where the values are in decreasing order. Organic carbon is significantly higher in Sungai Duku than in the Merambong areas while chlorophyll-a concentration shows a contrast result. Meiobenthic communities are separated spatially between stations where the community in Sungai Duku and Merambong Island is in higher abundance than in Merambong seagrass bed. Nematodes become the most dominant followed by the harpacticoids in both Sungai Duku and Merambong seagrass beds. The harpacticoid dominance is replaced by the amphipods in several quadrates in pulau Merambong. Vegetation such as seagrass and mangroves might improve the bottom condition thus supports the existence of harpacticoids and other meiobenthos in the estuary of Sungai Pulai.